Anatomical Relationship between Bl23 and the Posterior Ramus of the L2 Spinal Nerve. Issue 2 (April 2016) - Umemoto, Kanae; Saito, Toshiyuki; Naito, Munekazu; Hayashi, Shogo; Yakura, Tomiko; Steinke, Hanno; Nakano, Takashi
Background: The acupuncture point BL23 is located in the region of the posterior ramus of the second lumbar spinal nerve (L2) and has historically been used to treat conditions such as lower back pain, pollakiuria, erectile dysfunction, dysmenorrhoea, tinnitus, and vertigo. Some of these treatment effects have been hypothesised to be mediated by the sympathetic nervous system. It was recently discovered that the posterior ramus of the spinal nerve (PRSN) at L2 forms not two but three branches. Objective: To examine the relationship between the acupuncture point BL23 and the L2 PRSN in order to consider the pathways possibly affected by BL23 acupuncture. Methods: Acupuncture needles were inserted through the skin at BL23 to a depth of 3 cm a total of 13 times in eight donor cadavers (seven right-sided, six left-sided). Leaving the needle in place, ventral dissection was performed to determine the PRSN anatomy between the L1 and L3 spinal segments. In four cadavers, the relationship between the L2 spinal nerve and sympathetic branches was additionally evaluated. Following dissection, three-dimensional (3D) data were acquired using a photo scanner and 3D structural images were created using 3D computer graphics software. One additional (female) cadaver was studied without insertion of an acupuncture needle (due to significant scoliosis). Results: The L2 PRSN was divided into medial, intermediate and lateral branches. The needle inserted at BL23 came to lie in the region of the intermediate or lateral branches in all cases. Rami communicantes were found between the L2 spinal nerve and sympathetic trunk with fibres going on to supply the superior hypogastric plexus. Conclusions: Our findings suggest that acupuncture needles inserted at BL23 come into close proximity with the intermediate or lateral branch of the L2 PRSN, which could result in stimulation of both the somatic and sympathetic nervous systems.